2016
DOI: 10.13171/mjc.5.1/0160112/kirsch
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Molecular modeling of some new chalcones derived from coumarine as CDC25 phosphatases inhibitors

Abstract: New chalcones derived from coumarines were synthesized and tested as CDC25 phosphatase inhibitors. Molecular modeling of these new compounds was also presented in aim to study the mode of compounds orientation within CDC25 A and B. The reversibility of compounds 3, 4 and 5 was confirmed by application of MALDI-TOFMS technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Delel et al [103] reported the anticancer activity of coumarin-chalcones against CDC25 phosphatase. Hybrids with chlorine and bromine at the 6 th position on coumarin ring (21) inhibit CDC25A than hybrids with methoxy group at the 6 th position of coumarin ring.…”
Section: Anticancer Activitymentioning
confidence: 99%
“…Delel et al [103] reported the anticancer activity of coumarin-chalcones against CDC25 phosphatase. Hybrids with chlorine and bromine at the 6 th position on coumarin ring (21) inhibit CDC25A than hybrids with methoxy group at the 6 th position of coumarin ring.…”
Section: Anticancer Activitymentioning
confidence: 99%